2015
DOI: 10.1186/s13000-015-0309-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26b inhibits cell proliferation and cytokine secretion in human RASF cells via the Wnt/GSK-3β/β-catenin pathway

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic systemic auto- immune disease characterized by joint synovitis. Recent evidence suggests that rheumatoid arthritis synovial fibroblasts (RASFs) promote joint destruction. In this study, we investigated the role of microRNA-26b (miR-26b) in cell proliferation and inflammatory cytokine secretion using patient-derived Rheumatoid arthritis fibroblast-like synoviocyte (RAFLS) to understand pathways influencing rheumatoid arthritis.MethodsRAFLS were cultured in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…By inhibiting the GSK‐3β expression, miR‐26b was identified as an activator of Wnt signaling through inducing β‐catenin and cyclin D1. This activation resulted in reduced proliferation and increased apoptosis of FLSs as well as the synthesis of inflammatory mediators from FLSs . Aberrant expression of miR‐221, miR‐222 and miR‐323‐3p was seen in RA FLSs, and miR‐323‐3p regulated the Wnt signaling positively in RA FLSs through suppressing beta‐transducin repeat containing E3 ubiquitin protein ligase, which is involved in repressing the accumulation of β‐catenin …”
Section: Noncoding Rnas In Ra Flssmentioning
confidence: 99%
“…By inhibiting the GSK‐3β expression, miR‐26b was identified as an activator of Wnt signaling through inducing β‐catenin and cyclin D1. This activation resulted in reduced proliferation and increased apoptosis of FLSs as well as the synthesis of inflammatory mediators from FLSs . Aberrant expression of miR‐221, miR‐222 and miR‐323‐3p was seen in RA FLSs, and miR‐323‐3p regulated the Wnt signaling positively in RA FLSs through suppressing beta‐transducin repeat containing E3 ubiquitin protein ligase, which is involved in repressing the accumulation of β‐catenin …”
Section: Noncoding Rnas In Ra Flssmentioning
confidence: 99%
“…These results suggest that miR‐26b is likely to play an important role in development and maintaining cardiac function. Previous studies have also shown that miR‐26b could regulate β‐catenin levels by inhibiting Gsk3β, then affected the Wnt/Gsk3β/β‐catenin axis to elevate rheumatoid arthritis synovial fibroblasts (RAFLS) apoptosis and reduce the secretion of TNF‐α, IL‐1β and IL‐6 to inhibit the inflammation . Although miR‐26b plays a potential role in the regulation of the Wnt signalling pathway by targeting Gsk3β in RAFLS, whether it can mediate Wnt signalling to regulate the cardiomyocyte differentiation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) has been affecting 1% of the world's population [Schellekens et al, ]. It is known as a common autoimmune disease, with main characteristics of joint swelling, cartilage destruction, joint stiffness, and deformity [Sun et al, ; van der Geest et al, ; Prete et al, ; Smigielska‐Czepiel et al, ]. Current therapeutic methods of RA are prone to invasive antirheumatic therapy in the early phase of the pathogenesis.…”
mentioning
confidence: 99%